Medical tourism in Egypt: Opportunities and challenges - Ayoub, Magdi (AUC Knowledge Fountain, 2018)
Several developed and developing countries recognize medical tourism as a lucrative opportunity to generate national income and boost up the economy, which contribute to the overall development strategy. Although Egypt is well-positioned as tourism destination, medical tourism is lagging when compared to regional and global competitors. This thesis describes the status quo of Egypt’s medical tourism, analyze the strengths, weaknesses, opportunities and threats of medical tourism industry in Egypt, and define the required policies, entities and strategic plans needed to realize the goal of having a strong and competitive medical tourism industry. The study utilizes qualitative research methods using semi-structured interviews with several stakeholders in the medical tourism industry in Egypt including those in the Ministry of Health, Egyptian Tourism Authority, healthcare providers and medical tourism facilitators as a primary source for data related to medical tourism sector in Egypt, as well as several secondary data in published literature about this topic. The study analyzed Egypt’s competitive advantage of its medical tourism industry using the strengths, weaknesses, opportunities and threats (SWOT) analysis tool, based on the integrated model of medical tourism. Findings demonstrate that Egypt’s medical tourism industry has a number of strengths like the existing and well developed tourism infrastructure, abundance of healthcare professionals, and the great geographical location. On the other hand weaknesses are mainly related to the absence of medical tourism governance, poor marketing, low quality of healthcare, and the non-availability of educational programs that enhance the capacity of service providers to handle this type of tourists. A set of policy recommendations had been suggested, that aim to define a comprehensive development strategy for the sector and eventually will enhance the competitive advantage of medical tourism in Egypt.